Hubungan Penempatan dengan Kepuasan Kerja Pegawai di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Meyza Dri Alvia; Nelfia Adi; Nurhizrah Gistituati; Nelitawati Nelitawati (Journal of Educational Administration and Leadership, 2021)
Abstract This data assessment is an employee job satisfaction, employee placement and employee placement relationship with employee job satisfaction. This type of data assessment is qualitative research and uses descriptive methods. The way to accumulate data is interviews, questionnaires, observations. Data analysis is done using correlation techniques. The results showed that employee job satisfaction there is a high category with a percentage of 81.25%. Employees Placement sits on the fairly appropriate category with a percentage of 79.84%. obtained a meaningful bond on the sidelines of employee placement and on the excitement of power in agencies Archiving Office and Library West Sumatra Province where the significance value is 0.000 at a significant level of 5% or at a level of 95% trust. From the results of the correlation calculation, 0.000 <0.005. The criteria in the hypothesis test state that if the results of its significance are